ANALISIS HUBUNGAN SERTIFIKASI EKOLABEL TERHADAP MUTU DAN PRODUKSI UDANG VANNAMEI (Litopenaeus vannamei) PT YSI, BUTON TENGAH - Fatah Khoerudin; Hary Tjahja Soedibya; Purnama Sukardi; Taufik Budhi Pramono; Endang Hilmi (Universitas Mataram, 2024)
Ecolabel certification is one of the requirements that must be met to export vannamei shrimp (Litopenaeus vannamei) with European and American destination countries. The research method uses a mix method (qualitative and quantitative). The sampling technique uses the Global Aquaculture Alliance-Best Aquaculture Practices (GAA-BAP) checklist. Data were collected using observation techniques, in-depth interviews, and literature studies. Data analysis uses descriptive analysis with primary and secondary data approaches. The total value of GAA-BAP application in PT YSI's vannamei shrimp pond for the critical questions category and the scored questions category is above the minimum percentage of achievement of GAA-BAP ecolabel certification by obtaining a total value of 96.4% and 90.6%. The results of quality testing of vannamei shrimp cultivated by PT YSI show that vannamei shrimp meet the criteria for GAA-BAP ecolabel certification. PT YSI's cultivation performance is in accordance with the company's target by obtaining an average harvest of 2.1 tons/pond and a total harvest of 61,488 kg/30 ponds with a productivity value of 50.5 tons/ha of 20m² diameter ponds. This can be achieved with FCR values of 1.68, SR 92.80%, ADG 0.26, MBW 22.8 gr, average size 43 and total feed 103,603 kg. The average water quality value is DO 5.12 mg/l, temperature 32 °C, salinity 38 ppt and pH 7.8.